Revisiting nickel-catalyzed carbonylations: (unexpected) observation of substrate-dependent mechanistic differences - Lichtenberger, Niels; Menche, Maximilian; Rück, Katharina; Paciello, Rocco; Schäfer, Ansgar; Comba, Peter; Hashmi, A. Stephen K.; Schaub, Thomas (Organometallics, 2022)
The (hydroxy)carbonylation of tertiary aliphatic alcohols and their corresponding olefins with a Ni-based catalyst system is investigated. This study builds on a previous mechanistic investigation into the Ni-catalyzed carbonylation of alcohols. The findings differed from what could be explained with the previously reported mechanisms, prompting this in-depth mechanistic study. Combined experimental and quantum chemical efforts are crucial for the rationalization of the observed reactivities and ultimately help reveal another isobutene-based catalytic pathway, accessible with these substrates. This study further expands the knowledge about Ni-catalyzed carbonylation reactions, which have been known for more than 70 years but were scarcely studied in detail from a mechanistic point of view.
Gesehen am 06.07.2022